2014
DOI: 10.2166/wst.2014.048
|View full text |Cite
|
Sign up to set email alerts
|

Distillery fusel oil as an alternative carbon source for denitrification – from laboratory experiments to full-scale applications

Abstract: Industrial waste products may be a viable alternative to commercial external carbon sources. In this study, the properties of fusel oil (distillery waste product) were investigated in terms of temperature dependency of denitrification and acclimation period. Furthermore, results obtained during three different full-scale trials were used to verify similarities with and differences from the results obtained under laboratory-scale conditions. Batch experiments with non-acclimated biomass revealed a very strong t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…The initial NURs for the non-adapted activated sludge from the Poznan WWTP were comparable to the NUR values measured in our previous lab scale studies, also for not The initial NURs for the non-adapted activated sludge from the Poznan WWTP were comparable to the NUR values measured in our previous lab scale studies, also for not acclimated biomass to an external carbon source [20]. After adaptation to fusel oil, the NUR obtained in this study (2.7 mg NO 3 -N/g VSS•h) was significantly lower in relation to the values obtained in lab-scale experiments, where the NUR was as high as 16.0 mg NO 3 -N/g VSS•h [20,22].…”
Section: Kinetics Of Denitrification During the Acclimation Experiments Effectsupporting
confidence: 84%
See 3 more Smart Citations
“…The initial NURs for the non-adapted activated sludge from the Poznan WWTP were comparable to the NUR values measured in our previous lab scale studies, also for not The initial NURs for the non-adapted activated sludge from the Poznan WWTP were comparable to the NUR values measured in our previous lab scale studies, also for not acclimated biomass to an external carbon source [20]. After adaptation to fusel oil, the NUR obtained in this study (2.7 mg NO 3 -N/g VSS•h) was significantly lower in relation to the values obtained in lab-scale experiments, where the NUR was as high as 16.0 mg NO 3 -N/g VSS•h [20,22].…”
Section: Kinetics Of Denitrification During the Acclimation Experiments Effectsupporting
confidence: 84%
“…1,700,000 g O 2 /m 3 ) and a favorable COD/TN ratio (approximately 1800). It was found that 2-methyl-1-butanol was a dominant component of fusel oil (almost 40% by weight), with three other important components: 2-methyl-1-propanol, 3-methyl-1-butanol and ethanol [22].…”
Section: Characterization Of Fusel Oil Used As An External Carbon Sourcementioning
confidence: 99%
See 2 more Smart Citations
“…The aim of this study was to investigate changes in the metabolic activity of the DPAOs under anaerobic/anoxic conditions in response to addition of a distillery waste product (fusel oil). This compound is potentially a very favorable carbon source for denitrification due to the advantageous composition, i.e., high chemical oxygen demand (COD) concentrations and high COD/N ratios, which has been confirmed in a few earlier studies [ 20 , 21 ]. However, the anoxic interactions between denitrification and EBPR in the presence of fusel oil have not been reported so far.…”
Section: Introductionmentioning
confidence: 72%